Combatting Ghosting in Synchronous Online Learning: Efficacy of Project-Based Learning on Biology Students' Achievement, Creative Thinking Skills, and Engagement - Rahayu, Ucu; Kismiati, Dyah Aniza; Noviyanti, Mery; Sudarso, Yos; Abd Karim, Rafidah (Jurnal Pendidikan IPA Indonesia, 2025)
The phenomenon of ghosting in synchronous online learning, which indicates student disengagement, negatively affects student achievement. This study aims to assess the effectiveness of the Project-Based Learning (PjBL) model in improving student academic achievement, creative thinking skills, and engagement in synchronous online learning environments. A mixed-method, pre-experimental design with a one-group pretest-posttest approach was employed. The participants were enrolled in an Environmental Education course delivered through synchronous online tutorials (webinars). The PjBL model was implemented in six stages: posing essential questions, designing project plans, scheduling tasks, monitoring project activities and progress, assessing outcomes, and evaluating the learning experience. Data were analyzed using descriptive statistics. The results revealed that the PjBL model improved student learning outcomes at a low level, significantly enhanced creative thinking skills, and greatly increased student engagement. The study concludes that the PjBL model is a promising pedagogical approach for enhancing synchronous online learning experiences and fostering student cognitive development.